Targeted and Genomewide NGS Data Disqualify Mutations in MYO1A, the "DFNA48 Gene", as a Cause of Deafness. Issue 5 (31st March 2014) - Eisenberger, Tobias; Di Donato, Nataliya; Baig, Shahid M.; Neuhaus, Christine; Beyer, Anke; Decker, Eva; Mürbe, Dirk; Decker, Christian; Bergmann, Carsten; Bolz, Hanno J.
ABSTRACT MYO1A is considered the gene underlying autosomal dominant nonsyndromic hearing loss DFNA48, based on six missense variants, one small in‐frame insertion, and one nonsense mutation. Results from NGS targeting 66 deafness genes in 109 patients identified three families challenging this assumption: two novel nonsense (p.Tyr740* and p.Arg262*) and a known missense variant were identified heterozygously not only in index patients, but also in unaffected relatives. Deafness in these families clearly resulted from mutations in other genes (MYO7A, EYA1, and CIB2). Most of the altogether 10 MYO1A mutations are annotated in dbSNP, and population frequencies (dbSNP, 1000 Genomes, Exome Sequencing Project) above 0.1% contradict pathogenicity under a dominant model. One healthy individual was even homozygous for p.Arg262*, compatible with homozygous Myo1a knockout mice lacking any overt pathology. MYO1A seems dispensable for hearing and overall nonessential. MYO1A adds to the list of "erroneous disease genes", which will expand with increasing availability of large‐scale sequencing data.